2022
DOI: 10.1001/jamainternmed.2021.6352
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Specific Incidence of Cerebral Venous Sinus Thrombosis Associated With Ad26.COV2.S COVID-19 Vaccination

Abstract: Recent reports [1][2][3][4] suggest a possible association between Ad26.COV2.S (Johnson & Johnson/Janssen) COVID-19 vaccination and cerebral venous sinus thrombosis (CVST). Estimates of postvaccination CVST risk require accurate age-and sex-specific prepandemic CVST incidence rates; however, reported rates vary widely. 5 We compared the age-and sex-specific CVST rates after Ad26.COV2.S vaccination with the prepandemic CVST rate in the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 5 publications
1
12
1
1
Order By: Relevance
“…With regard to factors associated with increased risk of TE in the Covid-19 vaccine group, we found age as an important risk factor, adding a 5% increase risk for each year of age older, and we found no difference in risk between sexes. These findings are contrary to previous observations that found increased risk of a specific type of thrombosis (CVST) in younger women [27] . Most patients with TE in our series had classical risk factors (cancer, previous VTE, thrombophilia or recent surgery) and no manifestation of VITT, suggesting that events found have a different mechanism than the one described for VITT or no relation at all with the vaccines.…”
Section: Discussioncontrasting
confidence: 99%
“…With regard to factors associated with increased risk of TE in the Covid-19 vaccine group, we found age as an important risk factor, adding a 5% increase risk for each year of age older, and we found no difference in risk between sexes. These findings are contrary to previous observations that found increased risk of a specific type of thrombosis (CVST) in younger women [27] . Most patients with TE in our series had classical risk factors (cancer, previous VTE, thrombophilia or recent surgery) and no manifestation of VITT, suggesting that events found have a different mechanism than the one described for VITT or no relation at all with the vaccines.…”
Section: Discussioncontrasting
confidence: 99%
“…Production of soluble spike protein was caused by splicing events. Soluble spike protein has been found to cause an inflammatory response in endothelial cells [ 12 , 94 ]. A population-based cohort study estimated the risk of CVST after Ad26.COV2.S [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“… 8 Other reports have indicated that there was an increase in CVST incidence following the post-COVID-19 AstraZeneca and Johnson & Johnson/Janssen vaccination when compared to pre-pandemic incidence. 2 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…8 Other reports have indicated that there was an increase in CVST incidence following the post-COVID-19 AstraZeneca and Johnson & Johnson/Janssen vaccination when compared to pre-pandemic incidence. 2,9 The increase in incidence could be explained by pathophysiological changes thought to occur in VITT. CVST post-COVID-19 vaccination arises as a consequence of VITT.…”
Section: Discussionmentioning
confidence: 99%